2000
DOI: 10.1046/j.1464-410x.2000.00563.x
|View full text |Cite
|
Sign up to set email alerts
|

Is the conservative management of ureteric calculi of > 4 mm safe?

Abstract: Objective To determine the safety of the conservative management of ureteric calculi of >4 mm in diameter, using mercapto-acetyltriglycine (MAG3) radioisotope renography to monitor renal parenchymal function. Patients and methods Patients with symptomatic unilateral ureteric calculi were recruited prospectively. After con®rming the position of the stone using contrast urography, a MAG3 radioisotope renogram was taken within 48 h of admission and again 1 month after the patients became stone-free. The indicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
5

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 9 publications
(13 reference statements)
0
12
0
5
Order By: Relevance
“…Complications from an intervention for ureteral obstruction are much higher when symptoms exceed 4 weeks' duration. 15,16 Irreversible renal damage can occur with urinary obstruction that impairs renal function for over 2 weeks. 5,[29][30][31] In the US, the societal burden and indirect costs for lost wages from urolithiasis are estimated to be US$139 million annually.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Complications from an intervention for ureteral obstruction are much higher when symptoms exceed 4 weeks' duration. 15,16 Irreversible renal damage can occur with urinary obstruction that impairs renal function for over 2 weeks. 5,[29][30][31] In the US, the societal burden and indirect costs for lost wages from urolithiasis are estimated to be US$139 million annually.…”
Section: Discussionmentioning
confidence: 99%
“…The potential implications of a valid decision tool in this patient population are optimization and standardization of care, reduction of return ED visits and, ultimately, reduction in complications from delayed procedures. [13][14][15][16] Additionally, health care costs could be impacted by reduced complications, fewer ED visits and unnecessary referrals. Future studies to prospectively validate this model in another cohort of patients are important before we would advocate widespread clinical use of these predictors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Decreased renal function was found in 18% of patients, but only 2 patients who had had previous treatment for a calculus had persistent kidney impairment after stone removal. Finally, Irving et al 13 prospectively followed up 54 patients with ureteral calculi Ͼ4 mm and found that 28% of patients had silent loss of renal function, obligating treatment at diagnosis. For this particular group, they also studied the effect of treatment timing on the recovery of renal function, with better results when the intervention took place within the first week.…”
Section: 910mentioning
confidence: 99%
“…[44] . [45] . No ser humano, o tempo que o nefron tolera uma obstrução sem prejuízo permanente à sua função é controverso [46] .…”
Section: Cálculo Ureteral Silenciosounclassified